Analisis Kesesuaian Pengembangan Wisata Pantai Elak-Elak di Kabupaten Lombok Barat - Aprilya, Nabilah; Hilyana, Sitti; Amir, Sadikin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
The development of Elak-Elak Beach needs to consider the appropriate requirements for tourism activities. The suitability of coastal and marine resources aims to adapt to tourism activities, with the aim of preventing environmental damage in coastal areas due to tourism activities. Environmental problems in the aquatic environment (pollution) are caused by inappropriate activities in coastal environments such as tourism. This study aims to determine the suitability of Elak-Elak Beach for sustainable beach tourism and determine the carrying capacity value of the Elak-Elak Beach area. Data collection was carried out on December 6, 2023. The method used was field observation with the collection of tourism suitability data. The results of the measurement of the Tourism Suitability Index (TSI) are suitable for beach tourism, with the TSI value at 4 stations suitable for beach tourism, namely station 1 with a value of 2.825, station 2 of 2.595, station 3 of 2.22, and station 4 of 2.655. With a capacity for the category of beach recreation 214 people/day, sports tourism 136 people/day. camping 192 people/day, sitting relax 384 people/day, sunbathing 136 people/day, and swimming 315 people/day.